Kajian Keramahan Lingkungan Pukat Cincin pada KM. Berkah Sandrego 2 di Kepulauan Bangka Belitung - Misuari, Muhammad Nur; Dwikusuma, Agung; Suharyanto, Suharyanto; Mardiah, Ratu Sari; Irawan, Andi; Priyadi, Hermawan Gatot (Dept. Marine Science, 2026)
Maintaining the potential sustainability of fish resources in the sea, the government began “Code of Conduct for Responsible Fisheries (CCRF)” concept since it was adopted at the FAO Conference on October 31, 1995 to overcome irregularities in capture fisheries activities. The criteria for environmentally friendly fishing gear must have high selectivity, the gear does not damage the habitat, does not endanger the lives of fishermen, produces quality fish, the product does not endanger consumers, low by-catch, fishing gear provides minimal impact efforts on the diversity of biological resources, does not catch protected biota species that are threatened with extinction and is socially accepted by the community. The purpose of this study is to determine the environmental level friendliness of purse seines by means of observation, documentation, and interviews. The purse seine catches results in the study at KM. Berkah Sandrego 2 consists of Sardinella gibbosa by 25%, Amblygaster sirm by 27%, Selarodies leptolepis by 19%, Selar crumenophthalmus by 8%, Atule mate by 4%, Rastrelliger kanugarta by 6%, Euthynnus affinis by 9%, and other catches by 2%. The 88.32% catch total is the main catch (HTU), while 11.68% is bycatch (HTS) with total catch of fish that can be utilized at 100% and unutilized total catch at 0%. The assessment shows that this fishing gear is in the environmentally friendly category. The evaluation resulted in a score of 28 and a total score of 848, which proves that the purse seine is in the 28-36 category (very environmentally friendly).